Diálogo y sexualidad integral en los estudiantes de noveno de Básica en la Unidad Educativa Cicalpa. - Herrera Villalobos, Mirelia Leonor (2025)
The study aimed to analyze dialogue and comprehensive sexuality among ninth-grade students at the Cicalpa Educational Unit. The goal was to help young people perceive and understand terms related to sexuality, instilling a reasonable and responsible education. The importance of free, taboo-free communication was emphasized. Therefore, my research highlights the need to enhance knowledge in this area and thereby promote healthy and respectful sexuality. At this school, students were observed to be indifferent when it came to having conversations about sexuality. This negatively influences students. Due to this difficulty, they may make poor decisions, which would affect their academic development and future life plans. Given this difficulty, priority was given to administering a current survey, already approved by professionals in the Basic Education program. Likewise, adolescents are more concerned about their physical image, the way they look, and what they wear. Focusing on oneself; In this way, the level of understanding parents have regarding their children's sexual, reproductive, and emotional health was also determined. A quantitative approach was used, based on descriptive and correlational approaches, with a non-experimental, field-based, and bibliographic design. The study population consisted of 12 ninth-grade students. The data collection technique used was a survey, and the instrument was a structured questionnaire consisting of 10 questions, broken down into dialogue and comprehensive sexuality. This was compared to the project for the 2023-2024 school year, which used the same technique and instrument with the participation of 15 students. It was observed that the questions asked of the students strengthened, and with greater emphasis, communication between adolescents and their parents. Conclusions and recommendations are provided, which state that it is essential for young people to understand and recognize all the aforementioned aspects, thereby ensuring their full sexual development